“O mais profundo é a pele”: processos de construção de identidade por meio da tatuagem - Pereira, Beatriz Patriota (2016)
In order to contribute to the expansion of a sociological comprehension related to body and its identity, this research intents to understand how the inked person attributes meaning to his tattoo, to construct his identity. We recognize the increasing popularization of the tattoo and the existence of a correlation between tattoos and identity; also we consider that the tattoo, as a body modification, is a distinction and identification mark. Having those assumptions established, we propose in this research an understanding of the dimensions the tattoo has negotiated in a identity construction to the inked person. Those are our purposes: to understand how the tattoos meaning is built and the importance these signs hold in the selfimage construction to the inked person; to analyze how positions of subject, location and price influence in the process of choosing the images and the parts of the body in which the tattoo will be inked; finally, to establish the differences between “commercial” and “artistic” tattoos, both from the tattoo artist and the inked person point of view. These purposes will be achieved through a bibliographic, a participant observation in three different tattoo studios with different profiles and, finally, semi structured interviews with the tattooed persons.